Pomegranate (Punica Granatum L) Peel Powder as a Partial Replacement for Wheat Flour in Chocolate Cookies: Effect of Particle Size on the Physical and Antioxidant Properties (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study aimed to evaluate the effect of different particle sizes of pomegranate peel powder (PPP) as a partial replacement for wheat flour on the physical and antioxidant properties of cookies. The PPPs were prepared in three different particle sizes (1.0 mm, 0.5 mm, and 0.25 mm) and incorporated into cookies at a 15% substitution level. The physical properties of the cookies were evaluated, and the antioxidant properties were assessed in both dough and cookies to determine the effect of particle size on antioxidant retention after exposure to heat during baking. The particle size of PPP significantly affected the overall appearance, hardness, spread ratio, and colour of cookies. Reducing particle size decreased the cookie diameter and spread ratio, resulting in increased hardness. The appearance of the cookies became more compact and smoother with smaller particle sizes (0.25 mm) and exhibited a higher L* value. Furthermore, dough and cookies containing the smallest PPP particles (0.25 mm) exhibited significantly higher total phenolic content (TPC) values, DPPH radical scavenging activity, and ferric-reducing antioxidant power compared (FRAP) compared to samples with the largest particle size. This was attributed to the higher release of bioactive compounds due to the larger surface area. Baking caused some thermal degradation of antioxidants, resulting in slightly lower TPC and DPPH values in cookies than in dough. These findings highlight PPP's potential as a functional ingredient, enhancing the nutritional quality of cookies while reducing pomegranate peel waste.
Keywords: Pomegranate peel powder; Antioxidant properties; Particle size; Cookies